Global landscape of nutrition challenges in infants and children - Allen, Lindsay Helen 1946- (Nestlé Nutrition Institute Workshop series, 2020)
Malnutrition among children remains a persistent problem around the world. This publication aims to map the challenges within the global landscape of childhood nutrition and considers the importance of nutrition both prior to conception and in children beyond two years of age. Session I provides an updated picture of malnutrition around the world, the recent progress that has been made in eliminating malnutrition in all its forms and several data limitations to track such progress. The role of milk in early life is covered in session II. The chapters describe different aspects of cow's milk and the possible role of optimized plant proteins as an alternative to dairy ingredients in treating children with severe acute malnutrition. Session III considers the ramifications of environmental constraints to healthy child growth. The chapters cover the issue of how persistent gut damage and systemic inflammation can precipitate malnutrition as well as the putative effects of alterations in the gut microbiota. This overview of diverse issues is relevant to the epidemiology, biology of nutrition in early life, programmatic implications, and future directions.